(untitled) (Research, Society and Development, 2024)
Objective: To describe the immediate consequences of drought and dry spells in the health field, especially pharmaceutical care in Chaves Municipality, Marajó Island, Pará State. Methodology: This is an observational, cross-sectional, retrospective, ecological study, with August, September, and October 2024 as the time frame. Results: The demographic profile of the locations affected by drought and dry spells and their direct consequences for the population’s health are presented, especially regarding access to drinking water and medicines; as well as control, prevention, and intervention measures. To date, the total number of people affected by drought, dry spells, and salinization of water in rivers is approximately 8,050 people, bringing health problems as consequences; especially those related to infectious, gastrointestinal, respiratory, and dermatological diseases; as well as access to medicines. Conclusion: It can be inferred that the current situation of riverside communities in the municipality of Chaves, Marajó, Pará, is critical and requires a coordinated response, involving both emergency actions and short, medium, and long-term strategies to reduce the vulnerability of these populations.